Synthesis of an Alkyne-Modified Bleomycin Disaccharide Precursor, Conversion to a F-18-Labeled Radiotracer, and Preliminary in vivo-PET Imaging Studies - Sajal K. Maity; Cheng-Bin Yim; Satish Jadhav; Alejandra Verhassel; Johanna Tuomela; Olof Solin; Tove J. Grönroos; Pasi Virta (WILEY-V C H VERLAG GMBH, 2025)
The bleomycins (BLMs) are known antitumor antibiotics composed of the tumoricidal and tumor seeking domains. The peptide structure of BLMs is responsible for the cytotoxicity by selective oxidative cleavage of DNA (and RNA), while the tumor cell selectivity and internalization resides in the disaccharide moiety (i.e. BLM disaccharide). This has prompted researchers to utilize BLM disaccharide and its derivatives as constituents for the selective recognition of tumor cells, which may find further applications as new tumor imaging tools or drug delivery vehicles. In the present study a high yielding synthesis of an alkyne modified BLM disaccharide precursor that may be used as a useful agent for the click conjugation, its conversion to a F-18-labeled radiotracer, and preliminary in vivo PET imaging studies of the tracer with breast cancer (MCF-7) xenograft mouse models are described.